Validation and reliability of the Turkish version of the inflammatory bowel disease questionnaire for ulcerative colitis and Crohn’s disease - Kanı, Haluk Tarık; Ergenç, İlkay; Arıkan, Hüseyin; Kömesli, Zeynep; Seyrek, Berfin; Demirtaş, Coşkun Özer; Özen Alahdab, Yeşim; İmeryüz, Neşe; Atuğ, Özlen (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Inflammatory bowel diseases (IBD) impairs patients' quality of life (QoL). Inflammatory bowel disease questionnaire (IBDQ) is created to measure the health-related QoL specific for IBD. We planned to investigate the validation and reliability of the Turkish translation of IBDQ.Materials and Methods: Patients filled self-report questionnaires (Turkish Inflammatory bowel disease questionnaire (TrIBDQ) and Short Form-36 (SF-36)) themselves under a physician’s supervision, and they were free to ask questions about the questionnaires. The participants then filled the same questionnaire after at least two weeks. Construct validity, discriminant ability, reliability, and susceptibility to change were analyzed separately for the IBD patients. Intra-class correlation coefﬁcient (ICC) was used to assess test-retest reliability. Cronbach’s alpha values were used to assess internal consistency.Results: A hundred patients enrolled in the study, 53 with Crohn’s disease (CD), 47 with ulcerative colitis (UC). We found a moderate to high positive correlation between the TrIBDQ domains and the SF-36 dimensions. In UC and CD, TrIBDQ was able to differentiate active disease and remission. We found Cronbach’s alpha for TrIBDQ domains ranged from 0.76–0.94 in CD and from 0.79–0.92 in UC. The total Cronbach’s alpha for TrIBDQ was 0.96 in CD and 0.95 in UC. Sensitivity-to-change analyses of the bowel, systemic, and emotional scores showed statistically significant differences between their baseline and follow-up values.Conclusion: TrIBDQ is a valid and reliable tool for assessing the quality of life in Turkish speaking IBD patients. Thus it can be used in clinical research and practice.